2016
DOI: 10.1017/s000842391600038x
|View full text |Cite
|
Sign up to set email alerts
|

Did They Mind the Gap? Voter/Party Ideological Proximity between the BQ, the NDP and Quebec Voters, 2006–2011

Abstract: The 2011 Canadian federal election results changed the face of federal politics in Quebec. In a sudden and spectacular reversal of electoral fortunes, BQ support crumbled while that of the NDP surged. While most commentators focused exclusively on the 2011 election itself to explain what had happened, we offer an interpretation that takes a longitudinal approach. Using data from the Canadian Election Study and political party manifestos from 2006 to 2011, we propose a three-dimensional proximity model of voter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
(47 reference statements)
0
15
0
1
Order By: Relevance
“…Par exemple, l’émergence de nouveaux partis politiques comme l'Action démocratique du Québec et la Coalition avenir Québec ainsi que Québec Solidaire a réorienté en partie les débats politiques sur un axe gauche-droite ces dernières années. Malgré le fait que la question nationale structure le système partisan québécois de façon moins importante, il est important de souligner que cet enjeu continue néanmoins d'influencer significativement le vote de beaucoup d’électeurs québécois (Bélanger et Nadeau, 2009; Gauvin et al, 2016). De plus, l'importance du clivage souverainiste-fédéraliste demeure principalement une question empirique.…”
Section: Discussionunclassified
“…Par exemple, l’émergence de nouveaux partis politiques comme l'Action démocratique du Québec et la Coalition avenir Québec ainsi que Québec Solidaire a réorienté en partie les débats politiques sur un axe gauche-droite ces dernières années. Malgré le fait que la question nationale structure le système partisan québécois de façon moins importante, il est important de souligner que cet enjeu continue néanmoins d'influencer significativement le vote de beaucoup d’électeurs québécois (Bélanger et Nadeau, 2009; Gauvin et al, 2016). De plus, l'importance du clivage souverainiste-fédéraliste demeure principalement une question empirique.…”
Section: Discussionunclassified
“…Rather than use a unidimensional left-right framework, we have decided to test our hypotheses through the lens of three separate ideological dimensions. It has been argued that three separate ideological dimensions are necessary when examining vote choice in contexts with a strong ethnoregional divide: one that measures economic liberalism, one that measures social conservatism, and one that measures centralization (or preference for power to be concentrated at the centre in a society rather than at the periphery) (Gauvin, Chhim, and Medeiros 2016;Medeiros, Gauvin, and Chhim 2015;Wheatley et al 2014). This strategy also allows us to see a more complete picture of the ideological congruence of niche parties, as previous research has supported that a single left-right ideological dimension is too broad (Bischof and Wagner 2020).…”
Section: Datamentioning
confidence: 99%
“…Finally, we also control for the gender, the age, and respondent's ideological dispositions. Seeing as the literature has highlighted important issues with using a single ideological dimension (Albright ; Bakker ) and that recent work on the Quebec political landscape has demonstrated that exploring economic ideology and social ideology separately provides greater refinement (Medeiros et al ; Gauvin et al ), two attitudinal controls are also added to the analyses: economic ideology and social ideology. The former is a multi‐item variable constructed from questions that tap into respondents' attitudes towards daycare and corporate taxes.…”
Section: Datamentioning
confidence: 99%